Evaluasi Kebijakan Pemilihan Pesawat Terbang Polri dengan Menggunakan Analisis Technique of Order Preference by Similarity to Ideal Solution (Topsis): Evaluasi Kebijakan Pemilihan Pesawat Terbang Polri Dengan Menggunakan Analisis Technique Of Order Preference By Similarity To Ideal Solution (Topsis) - Stefanus Timonora Wahyu Ariyanto (Pusat Penelitian dan Pengembangan Polri, 2023)
This study aims to conduct a policy evaluation in selecting the main tool for the National Police in the form of airplanes using TOPSIS. Quantitative was chosen as the methodological choice using seven steps in the Technique of Order Preference by Similarity to Ideal Solution (TOPSIS) method. The data collection strategy was carried out by reviewing the aircraft documents to be selected and determining the criteria to be used. The data analysis technique is to use data processing in excel using the formula contained in the seven steps of the Technique of Order Preference by Similarity to Ideal Solution (TOPSIS) which is then included in the formula for each cell. Based on the analysis with the Technique of Order Preference by Similarity to Ideal Solution (TOPSIS), the results obtained were based on the calculation of the preference value (V), it was found that the largest preference value was 0.88. The ranking results show that the first order is the Boeing B737-900ER, the second is the Boeing B737-800, the third is the Airbus A-320 and the fourth is the Boeing 737-500. This shows that the most appropriate type of aircraft to choose is the Boeing B7373-900ER